Hindbrain rhombomere centers harbor a heterogenous population of dividing progenitors which rely on Notch signaling - Belmonte-Mateos, Carla; Meister, Lydvina; Pujades, Cristina (Frontiers in Cell and Developmental Biology, 2023)
Tissue growth and morphogenesis are interrelated processes, whose tight coordination is essential for the production of different cell fates and the timely precise allocation of stem cell capacities. The zebrafish embryonic brainstem, the hindbrain, exemplifies such coupling between spatiotemporal cell diversity acquisition and tissue growth, as the neurogenic commitment is differentially distributed over time. Here, we combined cell lineage and in vivo imaging approaches to reveal the emergence of specific cell population properties within the very same rhombomeres. We studied the molecular identity of hindbrain rhombomere centers, and showed that they harbor different progenitor capacities that change over time.By clonal analysis, we revealed that cells within the rhombomeres decrease the proliferative capacity to remain mainly in G1-phase. Proliferating progenitors give rise to neurons by asymmetric and symmetric neurogenic divisions, while maintaining the pool of progenitors.The proliferative capacity of these cells differs from their neighbors, and they are delayed in the onset of Notch-activity. By functional studies we demonstrated that they rely on Notch3signaling to be maintained as non-committed progenitors. In this study we show that cells in rhombomere centers might share steps of a similar program, despite the neurogenic asynchrony from the rhombomere counterparts, to ensure proper tissue growth.